Effects of murottal Arrohman decrease in blood pressure of pregnancy with preeclampsia at IRNA C Bangkalan Hospital - Iin Setiawati (NHM PRESS, 2020)
The proportion incidence of preeclampsia/eclampsia in East Java Province in 2010 was 26.92% which increased to 27.27% in 2011 and 34.88% in 2012. The high rate of preeclampsia can be prevented by conducting preeclampsia screening which is easy to do in the first and second trimester, by doing screening. Mean Arterial Pressure (MAP), Roll Over Test (ROT), Body Mass Index (BMI) in the basic health facility. Aims to analyze the effect of giving murottal arrohman to the reduction in blood pressure based on the ROT (Roll Over Test) and MAP (Mean arterial pressure) value in preeclampsia pregnant women. The method used was a true experimental research design using a pretest-posttest with control group design. The population was 64 pregnant women who experienced preeclampsia with a sample of 13 respondents using a probability sampling technique, with 13 respondents give murottal therapy and MgSO4 dan 13 respondents as group control which one therapy MgSO4. statistical test using One paired T-test with α (0,05). The instrument of this study used observation sheets. Murottal arrohman can decreased ROT to pregnancy with preeclampsia (p=.00). Murottal arrohman can decreased MAP to pregnancy with preeclampsia (p=.00). Murottal arrohman can decreased ROT dan MAP to pregnancy with preeclampsia in Irna C Hospital Bangkalan